Analysis of Causes for Extension of Time in Construction Projects: A Case Study of Kageshwori Manohara Municipality - Nepal, Sunil; Kumar Bhattarai, Subash; Sukamani, Dinesh; Nepal, Sujan (Kathford Journal of Engineering and Management, 2025)
Extension of Time (EoT) claims are a common occurrence in construction projects worldwide, often leading to disputes due to insufficient attention to delay causes during the contract initiation phase. However, in the context of Kageshwori Manohara Municipality, these challenges are particularly pronounced due to localized factors. This study identifies key causes of EoT through qualitative and quantitative analyses, utilizing Principal Component Analysis (PCA), Kaiser-Meyer-Olkin (KMO) testing, Bartlett's Test of Sphericity, Eigenvalue and variance analysis, and reliability assessments using Cronbach's Alpha. Principal Component Analysis (PCA) helped to categorize twelve major EoT causes into three components: Design and Consultant-Related Issues (Eigenvalue: 13.892, Variance: 55.57%), Project Management and Execution Challenges (Eigenvalue: 1.146, Variance: 4.58%), and External and Unforeseen Conditions (Eigenvalue: 1.000, Variance: 4.00%). Significant causes include inadequate design information, poor project management, and unforeseen challenges like land acquisition disputes. These causes were ranked using the Relative Importance Index (RII) to prioritize their impacts on project time extensions. The authors believe that present findings illuminate the need for improved design and planning processes, along with adaptive project management practices to mitigate EoT claims and enhance project performance within the municipality.